Alphabetti kinase Spaghetti: the complex roles of IKKα and β in the canonical NF-κB pathway. Issue 11 (17th June 2022) - Perkins, Neil D.
Abstract : Numerous studies, published over many years, have established the key role that the IκB kinase (IKK) subunits, α and β, play in regulating the Nuclear Factor κB (NF-κB) pathway. This research generally concluded that their functions can be separated, with IKKβ being the critical regulator of the canonical NF-κB pathway, while IKKα functions as the key activating kinase for the non-canonical pathway. However, other roles for these kinases have been described and several reports concluded that this separation of their functions may not always be the case. This commentary discusses the recent report by Biochem J. 479, 305–325, who elegantly demonstrate that in KRAS driven colorectal cancer cell lines, IKKα is an important regulator of the canonical NF-κB pathway. As is so often the case with trying to understand the complexity of NF-κB signalling, cellular context is everything.